2018
DOI: 10.1016/j.mcn.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Beta estradiol and norepinephrine treatment of differentiated SH-SY5Y cells enhances tau phosphorylation at (Ser396) and (Ser262) via AMPK but not mTOR signaling pathway

Abstract: Hyperphosphorylation of tau is one of the main hallmarks for Alzheimer's disease (AD) and many other tauopathies. Norepinephrine (NE), a stress-related hormone and 17-β-estradiol (E2) thought to influence tau phosphorylation (p-tau) and AD pathology. The controversy around the impact of NE and E2 requires further clarification. Moreover, the combination effect of physiological and psychological stress and estrogen alteration during menopause, which affect p-tau, has not been addressed. Exposure to E2 is believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The neuroblastoma cell line SH-SY5Y is human-derived 54 and cells can be differentiated with various substances into polarized neuronal cells (SH-SY5Y-derived neurons) at low cost 55 . SH-SY5Y-derived neurons express common neuronal maturation marker proteins [56][57][58][59][60][61] , including all six major human TAU isoforms 62,63 , show proper axonal TAU localization, and mimic the phosphorylation state of TAU in the adult human brain [64][65][66][67] . In brief, SH-SY5Y-derived neurons unite the benefits of a cell linei.e.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroblastoma cell line SH-SY5Y is human-derived 54 and cells can be differentiated with various substances into polarized neuronal cells (SH-SY5Y-derived neurons) at low cost 55 . SH-SY5Y-derived neurons express common neuronal maturation marker proteins [56][57][58][59][60][61] , including all six major human TAU isoforms 62,63 , show proper axonal TAU localization, and mimic the phosphorylation state of TAU in the adult human brain [64][65][66][67] . In brief, SH-SY5Y-derived neurons unite the benefits of a cell linei.e.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies in vitro showed that the microtubule-binding capacity of tau protein decreased by 35, 25, and 10%, respectively, after phosphorylation at Ser262, Thr231, and Ser235 sites. Therefore, the phosphorylation site of tau protein plays an important role in tau protein-induced neurodegeneration (Haase et al, 2004;Stokin and Goldstein, 2006;Majd et al, 2018). According to the latest research, an interdependent relationship hypothesis has been reported.…”
Section: Phosphorylation and Dephosphorylation Of Taumentioning
confidence: 99%
“…E2 treatment sustained tau hyperphosphorylation induced by protein kinase A activation in human embryonic kidney HEK293 cells stably expressing tau441 [ 96 ]. Similarly, it enhanced tau phosphorylation on several epitopes (Ser396, Ser262 but not Ser202/Thr205 (AT8)) through adenosine monophosphate protein kinase activation human SH-SH5Y neuroblastoma cells [ 97 ]. In contrast, it attenuated tau hyperphosphorylation at multiple sites (S396/404, Thr231, Thr205, S199/202) induced by transient GSK3β overexpression in mouse N2A neuroblastoma cells [ 98 ].…”
Section: Protective Effects Of Neuroactive Steroids On Ad-like Neumentioning
confidence: 99%